Public Debt Stock, Education-Centric Human Capital and Economic Growth in Nepal - Dahal, Madhav Prasad (Economic Journal of Development Issues, 2016)
Government borrows from domestic and foreign sources to finance its budget deficit. There are theories and empirical evidence that suggests negative effect of government debt on economic growth. By applying the autoregressive distributive lag (ARDL) approach to co integration on time series data of Nepal spanning over 1975-2014 , this study finds positive and statistically significant effect of total public debt on the GDP of the country. This result contradicts majority of the existing empirical literature. For the positive result we resort to Keynesian view on the effect of public debt in the economy. The total debt-to-GDP ratio of Nepal shows a declining trend. This should have some policy considerations in the conduct of fiscal policy in Nepal. The contribution of education-centric human capital on GDP is found positive as predicted by theory. Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 76-104